Proyecto de factibilidad para la creación de una empresa dedicada a la producción de licor seco (Malaqueño) de la parroquia Malacatos - Tacuri Ordóñez, Gina Belén (2023)
The main objective of the Curricular Integration Work, "FEASIBILITY PROJECT FOR THE CREATION OF A COMPANY DEDICATED TO THE PRODUCTION OF DRY LIQUOR (MALAQUEÑO) IN THE MALACATOS PARISH", is to determine the feasibility to create a company dedicated to dry liquor production in Malacatos in order to establish the technical, economic and financial feasibility. To create the company a feasibility project was developed, which begins with the elaboration of a market study data obtained through the application of surveys to the population of Malacatos, after the analysis of the information collected it was determined that in the parish there is an effective demand of 93% of the products, and an unsatisfied demand required by 568 people, which was used to determine the amount of production needed. As for the technical study, with the help of the macro location it was decided the most advantageous place to locate the company, on the other hand with the micro location was established the exact point where the products will be manufactured, which will be in the sector of the parish Malacatos, canton Loja, Santa Cruz neighborhood, at 200 m from the mining El Huato. Within the organizational study, the type of company to be incorporated was established in the first instance the RUC, the legal basis, and the structural and functional flow chart to be followed by the workers in order to carry out their activities. In the financial study, the initial capital was set at $145,647.96, which will be contributed by the company's partners; the external capital was set at $339,845.24 will be financed by the “Cooperativa de Ahorro y Crédito JEP”, for a total investment of $485,493.20. The Financial Evaluation determined the Net Present Value of $20,606.17; the Internal Rate of Return of 9.72; the Benefit-Cost Ratio of $ 1.28; the Capital Recovery Period of 4 years, 8 months and 2 days; and the sensitivity analysis shows that the project can support an increase in Costs of 0.49% and a decrease in Income of 0.40% in the location of the company. With the above information data, it is concluded that the implementation of the company is feasible, considering that the financial evaluation indicators are positive and ensure the investment; therefore, its due execution is recommended.